The Role of Educators and Parents in Individual Learning Programs for Early Age Children with Special Needs at School and at Home in Kembangan District, West Jakarta - Irma Yuliantina; Sukiman; Isyfan Rizqi Wahyunanda; Eni Nuraeni; Sri Daryani; Dyah Khoirunnisa (PT FORMOSA CENDEKIA GLOBAL, 2024)
The Community Service Program (PKM) aims to increase the role of educators and parents in supporting the Individual Learning Program (PPI) for early childhood children with special needs in Kembangan District, West Jakarta. This activity includes socialization, data collection through the distribution of assessment instruments, pre, posttest, BIMTEK, monitoring, evaluation. The method used involves observation, interviews. The implementation process lasted five months. The results show increased understanding of educators and parents, better synergy between school and home, as well as a positive impact on children's cognitive, social emotional, behavioral and motor development. This program has the potential to become a model for improving inclusive education in Indonesia, with a significant contribution to the PAUD environment in Indonesia.